Analisis Pengaruh Konsep Tri Kaya Parisudha Dan Sistem Pengendalian Internal Terhadap Kecenderungan Fraud (Kecurangan) - Ni Wayan Desya Dani Swari; Ni Wayan Yuniasih; Ni Wayan Alit Erlina Wati (Hita Akuntansi dan Keuangan, 2023)
This research was motivated by a fraud case in the form of embezzling customer funds worth Rp. 14,027,000 from one of the collectors. The area of this exploration is in KSP. Panca Tirta Rauh during the reign of Gianyar. The reason for this study was to examine the impact of the Tri Kaya Parisudha concept and internal control system on the tendency of KSP fraud. Panca Tirta Rauh, Gianyar. This study utilizes quantitative methods. The review population consisted of his 70 from all employees at his five KSP branches. KSP. Panca Tirta Rauh consists of administrators, cashiers, lifeguards and collectors. The sampling technique utilized is a saturation sampling method with an example size of 70 respondents. Information were gathered by interview and survey strategies and accordingly broke down utilizing various straight relapse investigation methods. The results of this study indicate that 1) the concept of Tri Kaya Parisudha has a significant negative impact on fraud propensity (fraud); 2) The internal control system has a significant negative impact on fraud.